2012
DOI: 10.1002/aqc.2221
|View full text |Cite
|
Sign up to set email alerts
|

The application of palaeolimnology to evidence‐based lake management and conservation: examples from UK lakes

Abstract: ABSTRACT1. To help meet the requirements of water legislation, palaeolimnology has been widely used to establish 'reference conditions' and restoration targets for lakes. However, its potential for assessing the necessity and appropriateness of different lake management activities has been less publicized.2. With reference to selected case studies covering consultancy projects commissioned by UK conservation agencies, this study highlights the important applied role of palaeolimnology. Using varying combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 46 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…Sayer et al . ). Based on the CE results, shared priorities might include thematic topics such as biodiversity (Willis et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sayer et al . ). Based on the CE results, shared priorities might include thematic topics such as biodiversity (Willis et al .…”
Section: Discussionmentioning
confidence: 97%
“…For instance, by designing LTE to address site‐specific lake management questions set by managers, palaeolimnologists were able to evaluate proposed management activities and make practical recommendations to improve their conservation effectiveness (Sayer et al . ). This can result in multi‐use solutions, such as identifying species conservation strategies that also maintain recreational fishing values (Sayer et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notwithstanding the taphonomic issues associated with the plant-macrofossil relationship arising from the varying reproductive strategies and dispersal capabilities of plants, several comparative studies of macrofossil records with botanical records have shown plant macrofossils to reliably record shifts in the dominant aquatic vegetation of shallow lakes (Davidson et al 2005;Salgado et al 2010;Clarke et al 2014;Levi et al 2014). Plant macrofossils have been variously employed to investigate long-term successional changes in the submerged vegetation of lakes (Bradshaw et al 2005;Rasmussen and Anderson 2005), responses to recent eutrophication (McGowan et al 2005;Salgado et al 2010;Sayer et al 2010a;Madgwick et al 2011) and top-down impacts of fish (Sayer et al 2016), and to inform on lake conservation status and the need for appropriate management (Sayer et al 2012;Wiik et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a better understanding of historic plant communities and any ecological changes that may have occurred is important in setting objectives for a particular lake, especially where anthropogenic impacts may have resulted in changes to the character of a site where its 'natural' condition or reference condition is in question. With a few notable exceptions (Ayres et al 2008;Sayer et al 2012;Kowalewski et al 2013;Wiik et al 2014;Clarke and Lynch 2016), however, there have been few applications of plant macrofossil analysis to directly inform conservation and management. This contrasts with the numerous applied palaeolimnological studies that have defined chemical reference conditions for lakes using transfer functions to assist in management decisions (Dixit et al 1999;Hall and Smol 2010;.…”
Section: Introductionmentioning
confidence: 99%